2013
DOI: 10.1177/2167696813515853
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in the Spillover Between Romantic Experiences, Work Experiences, and Individual Adjustment Across Emerging Adulthood

Abstract: This study examines the interplay between negative romantic experiences, negative work experiences, and anxiety/depressive symptoms at three time points across ages 24-29 in a sample of 176 Israeli emerging adults. Males (n ¼ 96) and females (n ¼ 80) described different patterns of longitudinal spillover between work, romantic relationships, and well-being. For males, higher levels of negative romantic experiences predicted increases in negative work experiences, and higher levels of anxiety and depressive sym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 56 publications
3
12
2
Order By: Relevance
“…Finally, in line with our fourth postulate, despite some connections between the two domains, Israeli, German, and Argentinean studies all suggest that young people might treat work and romantic experiences as different domains where life meaning can be found and constructed and do not necessarily perceive them as connected (Facio & Resett, 2014;Seiffge-Krenke & Luyckx, 2014;Shulman, Laursen, & Dickson, 2014). This does not mean that emerging adults are either in a relationship or working.…”
Section: The Social and Cultural Conditions For Finding Meaning In Thsupporting
confidence: 60%
“…Finally, in line with our fourth postulate, despite some connections between the two domains, Israeli, German, and Argentinean studies all suggest that young people might treat work and romantic experiences as different domains where life meaning can be found and constructed and do not necessarily perceive them as connected (Facio & Resett, 2014;Seiffge-Krenke & Luyckx, 2014;Shulman, Laursen, & Dickson, 2014). This does not mean that emerging adults are either in a relationship or working.…”
Section: The Social and Cultural Conditions For Finding Meaning In Thsupporting
confidence: 60%
“…The first goal of this study was to extend the existing literature on the negative effects of stress on relationship satisfaction by investigating emerging adults in dating relationships, and the possible protective role of self-control. Our results confirm the patterns previously reported for married couples (see Karney & Neff, 2013;Randall & Bodenmann, 2017), and for dating relationships in emerging adulthood (Falconier et al, 2015;Shulman, Laursen, & Dickson, 2014). Emerging adults in our study who reported greater percieved stress also reported lower relationship satisfaction.…”
Section: Discussionsupporting
confidence: 92%
“…Further, although the identity development literature centers squarely on adolescence and emerging adulthood, somewhat ironically, researchers here have left gender relatively underexamined in comparison to other domains of identity, such as ethnic identity (e.g., Umaña-Taylor et al, 2014), or content domains such as religion or relationships (e.g., McLean et al, 2014; McLean, Syed, & Shucard, 2016). Thus, we situated this study in emerging adulthood, a time when individuals are exploring culturally salient adult roles such as family and work-related issues (see Mayseless & Keren, 2014), which are tightly linked to gender norms (e.g., Archer, 1989; Frisén & Wängqvist, 2011; Shulman, Laursen, & Dickson, 2014).…”
Section: Gender and Developmentmentioning
confidence: 99%